COMPARISON OF VALIDITY OF FNACAND ZIEHL–NEELSEN STAINS IN DIAGNOSING CERVICAL TUBERCULOUS LYMPHADENITIS - Qaiser, Aisha; Niazi, Muhammad Babar Sohail; Hassan, Zaheer Ul; Khattak, Shahid Farroq; Iqbal, Shahid; Akbar, Sunarays (Pakistan Armed Forces Medical Journal, 2021)
Objective: To compare the validity of FNAC & ZN staining in diagnosing tuberculous lymphadenitis taking mycobacterial culture as gold standard.Study Design: Cross sectional study.Place and Duration of Study: Pathology department, Fauji Foundation Hospital Peshawar, from Oct 2019 to Sep 2020.Methodology: This study includes 100 patients with enlarged cervical lymph nodes who presented as outdoor patients. After routine baseline & radiological investigations, FNAC & ZN staining was carried out, followed by mycobacterial culture.Results: FNAC of tuberculous patients was positive in 56 (56%) patients while 24 (24%) patients revealed posi-tive mycobacterial culture. Inpatients with positive culture, 77 (77%) were FNAC positive and 23 (23%) were negative on cytology.Conclusion: Fine needle aspiration is more sensitive & specific test than Ziehl-Neelsen staining.